An evaluation of lifestyle changes in cancer patients after diagnosis - (:unkn) unknown (ZERBINIS MEDICAL PUBL, 2013)
Purpose: Cancer is an increasingly important health problem, and is second only to cardiovascular disease as cause of death. Cancer diagnosis causes significant changes in patients and their families, and social relationships are affected. For this reason, we examined the lives of patients subsequent to their diagnosis and sought to determine any changes in their lifestyles. Methods: Between March 16th and September 30th, 2011, a questionnaire consisting of 20 questions was distributed via a face-to-face interview to 150 patients at the Marmara University Hospital Oncology Unit. Each patient was queried during the administration of his/her chemotherapy. Six of the questions were independent choices, and 14 were dependent (multiple choice). A Local Ethics Committee approval was obtained. Results: Of the 150 patients, 70 (46%) were male and 80 female, and their median age was 55 years (range: 22-82).Following their diagnosis, 71% of males and 50% of females reported that they were complying with guidelines for a healthy lifestyle, and 19% of the patients said that they were eating healthier food. At the time they filled in the questionnaire, 61% said that they were hopeful; however, close to 10% said that they felt hopeless. Approximately 53% of the participants said that following their diagnosis they had a more sympathetic view of the underserved and underprivileged. Conclusions: It was surprising that an unexpectedly high percentage of the respondents reported that they did not make any changes in their lifestyles after their diagnosis of cancer, including eating healthier food. It appears Turkish cancer patients are coping with cancer in different means and ways than we expected of them.
Keywords: cancer; change; chemotherapy; lifestyle; media; psychological status; BREAST-CANCER; TRUTH